Exploring the Diversity of Archipelago Ornaments through Contemporary Motifs and Digital Techniques for Textile Design - Wesnina, Wesnina; Prabawati, Melly; Noerharyono, Muchamad; Putri, Vivi Radiona Sofyani (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
This study aims to (1) provide detailed descriptions of traditional Indonesian themes that inspire contemporary Indonesian batik motifs and (2) create modern Indonesian designs influenced by batik and weaving through digital textile design techniques. A qualitative approach is employed, utilizing applied research analytic tools. The analytical technique of practice-led research involves stages such as preparation, envisioning, developing imagination centered on idea maturity, and craftsmanship. Data analysis processes include data reduction, data display, and conclusion drafting. The analysis stage produces designs characterized by excessiveness, maximalism, dominance, extra-large size, hyperbole, and distortion, incorporating light colors, contrast, sparkle, and dark effects with patronizing motifs (floral/animal patterns). Additionally, 40 motifs were developed based on variations in color and size. Specifically, KS.06 and KS.07 showed that the bamboo shoot motifs were disproportionate to the cloth size, while in KS.04, the motifs appeared overcrowded when printed. The fabric fibers in the motifs of TK.04 and TK.06 were printed at a slant, resulting in a high elongation level. This research aims to enrich the archipelago's design references using cultural and geographical elements. Theoretically, it contributes to the literature for academia and the fashion industry, fostering creativity and the development of meaningful motifs.